The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/bcp.14818
|View full text |Cite
|
Sign up to set email alerts
|

A safety signal of somnambulism with the use of antipsychotics and lithium: A pharmacovigilance disproportionality analysis

Abstract: Aims Antipsychotics and lithium are widely used in psychiatry, particularly in schizophrenia and bipolar disorders. Recently, some cases of somnambulism or sleep‐related eating disorder (SRED) have been reported in patients treated with these drugs. This study investigated the risk of reporting somnambulism or SRED associated with the use of antipsychotics and lithium. Methods The World Health Organization pharmacovigilance database (VigiBase), comprising >18 million adverse events, was queried. All somnambuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…VigiBase is the World Health Organisation (WHO) global database that collects potential side effects of medicinal products 10 . Many studies have been carried out on psychotropic drugs, including antipsychotics, based on data extracted from the VigiBase 11,12 . Moreover, early signals of drug abuse have already been highlighted using data from the VigiBase database 13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…VigiBase is the World Health Organisation (WHO) global database that collects potential side effects of medicinal products 10 . Many studies have been carried out on psychotropic drugs, including antipsychotics, based on data extracted from the VigiBase 11,12 . Moreover, early signals of drug abuse have already been highlighted using data from the VigiBase database 13 …”
Section: Introductionmentioning
confidence: 99%
“…10 Many studies have been carried out on psychotropic drugs, including antipsychotics, based on data extracted from the VigiBase. 11,12 Moreover, early signals of drug abuse have already been highlighted using data from the VigiBase database. 13 The objective of this study was to analyse the worldwide data collected in the VigiBase database to identify potential abuse/misuse signals concerning SGAPs.…”
Section: Introductionmentioning
confidence: 99%
“…One-fifth of the SRED cases are related to AAPs. Quetiapine, ziprasidone, aripiprazole, lurasidone, and olanzapine have been associated with SRED [37,38]. Quetiapine stands out in terms of number of cases and disproportionality.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22] On the other hand, a recent large pharmacovigilance analysis reported a significant signal of SWor sleep-related eating disorders (SREDs) associated to second-generation antipsychotics, mainly to quetiapine and olanzapine, followed by aripiprazole, even if almost all secondgeneration antipsychotics, except risperidone and paliperidone, were associated with SW or SRED. 11 Psychiatric disorders, such as schizophrenia, bipolar disorder, and depression, are also associated with parasomnias, and they may increase the chance of SW. 18 However, to our knowledge, there are no previously reported cases of olanzapine-related somnambulism in eating disorders (EDs).…”
mentioning
confidence: 99%
“…3 Somnambulism can be the consequence of psychological stress, abnormal breathing during sleep, high fever, or drug adverse effects. 4 Indeed, previous studies reported several kinds of drug-related somnambulism, including zolpidem, 5 paroxetine, 6 bupropion, 7 valproate, 8 topiramate, 9 lithium, 10,11 propranolol, 12 and first- 13,14 and secondgeneration 11,15 antipsychotics. Indeed, the association between drugs and SW is well documented, 16 and even somnambulism as a result of second-generation antipsychotic treatment has been previously reported.…”
mentioning
confidence: 99%